Features of emotional burnout by specialists in assisting professions: Особливості емоційного вигоряння у фахівців допомагаючих професій - Astremskaya, Irina (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2019)
The article deals with the problem of "professional exit", which is referred to as "professional benefits" in the activities of specialists professionals. The peculiarities of professional activity of teachers and psychologists of educational institutions, which complicate the work of the specified category of specialists, are considered. Particular attention is paid to the syndrome of "professional burnout" among pedagogical workers of educational institutions for children with physical and psychiatric disabilities due to the fact that their professional activities are deeply. Specific and emotionally tense.
Keywords: professional burnout syndrome; psychological protection; teacher; vocational assistance